Batik Wastewater Treatment Using Simultaneous Process of Electrocoagulation and Electro-Assisted Phytoremediation (EAPR) - Rudy Syah Putra; Aprilia Dwi Annisa; Sigit Budiarjo (Universitas Gadjah Mada, 2020)
The aims of the study are to identify the effectiveness of wastewater treatment from the Batik industry using a simultaneous of electrocoagulation (EC) and electro-assisted phytoremediation (EAPR). Rough horsetail (Equisetum hyemale) was used as an accumulator plant in the EAPR system. Electrocoagulation was conducted for 1 h at a constant voltage of 20 V in 10 L solution, while EAPR was processed for 7 day at a constant voltage of 5 V in 17 L solution. The chemical oxygen demand (COD) of water was determined by closed reflux of colorimetric methods and heavy metal concentration was determined by flame-atomic absorption spectrophotometer. The results showed that the COD decreased by 69.6% after 1 h of electrocoagulation process and up to 80.9% after the EAPR process. The concentration of Cr and Pb decreased as much as 25% and 8.52%, respectively in the similar process. The simultaneous process could extend the heavy metal removal up to 0.28 mg/L for Cr and 0.09 mg/L for Pb in liquid wastewater from the initial concentration. These results showed that the levels of COD and heavy metal concentration in Batik wastewater have reduced in accordance with the Ministry of Environment Decree No. 5/2014 Republic of Indonesia regarding various industries wastewater standard with the threshold limit of 150 mg/L for COD and 1.0 mg/L for Cr on textile industry and 0.1 mg/L for Pb on Class I for another wastewater standard. The estimated cost of operation was US 1.509 m–3 indicating the viability of Batik industry wastewater treatment.